The resistance to axial dislodgement of nickel titanium compression arch wire hooks - an in vitro study - Karsten Agneta Linder-Aronson; Forsberg Carl-Magnus; Öberg Martin (Sciendo, 2019)
To evaluate the level of force required to axially dislodge nickel titanium compression hooks (Trillium Compression HookTM, Hespeler Orthodontics) placed on orthodontic arch wires in vitro.